Penile necrosis requiring penectomy complicating recto-urethral fistula post prostate cancer external beam radiation and brachytherapy - Kinahan, John; Pai, Howard; Martens, Mildred; Gray, Jason; Biberdorf, Darren; Mihailovic, Alex; McAuley, Iain (Canadian Urological Association Journal, 2014)
Radiation therapy is a well-recognized treatment for unfavourable risk localized prostate cancer. Radiation induced recto-urethral fistulae are known rare complications particularly from brachytherapy. We report a case of a recto-urethral fistula 7 years post-external beam radiation and I-125 brachytherapy, which was complicated by a severe polymicrobial soft tissue infection. This infection required penectomy and pelvic exenteration with diverting colostomy, Indiana pouch urinary diversion and gracilis myocutaneuos flap closure of the perineum.